Investigation of the effects of fascia lata on neochondrogenesis in a rabbit model - Yılmaz, Şengül; Bilkay, Özge; Özdemir, İsmail; Avcı, Arzu; Adadan Güvenç, Işıl (ENT Updates, 2014)
Objective: The impact of fascia lata on neochondrogenesis placed between both leaflets of the perichondrium after full thickness submucoperichondrial cartilage resection was investigated in a rabbit septum model. Methods: Twenty adult New Zealand rabbits were studied in two groups with equal number of animals in each group. Full thickness cartilage with an area of 1 cm2 was resected to create a cartilage defect in all rabbits. Autogenous fascia lata was interposed between both leaflets of the perichondrium and the surgical field was closed (fascia lata group). No material was interposed between both leaflets of the perichondrium of the defective area (control group). Rabbits were sacrificed on postoperative 90th days and their septa were totally excised. Neochondrogenesis was investigated histopathologically with a light microscope. The preparations were evaluated as for thickness of newly formed cartilage (in mm), inflammatory reaction and presence of macroscopic perforation. Results: Thickness of the cartilage in the fascia lata group was significantly greater than that of the control group (M-W-U=15,000, p<0.05). Conclusion: Use of fascia lata in the acceleration of perichondrial neochondrogenesis can result in successful outcomes in the repair of cartilage defects.